Production of Bioethanol from Office Waste via Simultaneous Saccharification Fermentation - Micky, Vincent; Hasni, H Nor; Ennry, Esut (Hibiscus Publisher, 2014)
Bioethanol is an attractive and sustainable fuel that can be used in the transportation sector. It is recognized as being a good alternative to conventional fossil based fuel as it is biodegradable and emits zero net carbon output into the atmosphere. In this study, bioethanol was produced from office waste by usinga commercial cellulase preparation and Saccharomyces cerevisiae via Simultaneous Saccharification Fermentation (SSF). The office waste feedstocks were loaded at 5.0%, 7.5% and 10.0% (w/v) against two cellulase dosages at 25 and 50 FPU/g paper. The fermentation products and residual sugars were then analyzed via High Performance Liquid Chromatography (HPLC). From the results obtained, the combination of 5.0% feedstock loading with 50 FPU/g paper cellulase produced the highest concentration of ethanol at 96 hr, which was at 67.64% of theoretical ethanol yield (TEY). Whilethe combination of 10.0% feedstock loading with 50 FPU/g paper cellulase produced the lowest concentration of ethanol at 32.69% of TEY. This study has shown that office waste can be converted to bioethanol via SSF, and may assist in reutilization and the waste management of office waste.